2009
DOI: 10.1186/1741-7007-7-16
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory parasites and toll-like receptor-mediated tumour necrosis factor alpha responsiveness in wild mammals

Abstract: Background: Immunological analyses of wild populations can increase our understanding of how vertebrate immune systems respond to 'natural' levels of exposure to diverse infections. A major recent advance in immunology has been the recognition of the central role of phylogenetically conserved toll-like receptors in triggering innate immunity and the subsequent recruitment of adaptive response programmes. We studied the cross-sectional associations between individual levels of systemic toll-like receptor-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(116 citation statements)
references
References 74 publications
3
113
0
Order By: Relevance
“…We used the restricted data set for the northern 'massif des Ardennes' where we previously found a significant association between PUUV and H. mixtum (Ribas . Several studies on laboratory mice and wild rodents have shown that a phylogenetically closely related helminth species, Heligmosomoides polygyrus, may be immunosuppressive (Jackson et al, 2009;Maizels et al, 2012). This suggested that infection with H. mixtum might modulate the immune responses of bank voles and change their susceptibility to PUUV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the restricted data set for the northern 'massif des Ardennes' where we previously found a significant association between PUUV and H. mixtum (Ribas . Several studies on laboratory mice and wild rodents have shown that a phylogenetically closely related helminth species, Heligmosomoides polygyrus, may be immunosuppressive (Jackson et al, 2009;Maizels et al, 2012). This suggested that infection with H. mixtum might modulate the immune responses of bank voles and change their susceptibility to PUUV.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, Heligmosomoıdes polygyrus bakeri has been shown to induce a wide spectrum of immunomodulatory effects in the laboratory mouse and to affect the outcome of infection with several pathogens, including nematodes, trematodes, protozoa and bacteria (see a recent review by Maizels et al, 2012). Jackson et al (2009) even showed, in wild wood mice (Apodemus sylvaticus), that the Tnf-a response to TLR ligands was downregulated by natural infection with H. polygyrus. It has been suggested that H. mixtum may also be immunosuppressive.…”
Section: Epidemiological Consequences For Puuv Infectionmentioning
confidence: 99%
“…However, maternal effects and other early-life experiences, including pathogen exposure, could contribute to these differences (Saino et al, 2002;Jackson et al, 2009;Morrison et al, 2009). For instance, maternal transfer of hormones or other molecules to eggs can influence physiological, behavioral and immunological phenotypes in offspring (Saino et al, 2002;Groothuis et al, 2005;Grindstaff et al, 2006;Gasparini et al, 2009;Hasselquist and Nilsson, 2009).…”
Section: Evolved Versus Plastic Differences In the Acute Phase Responsementioning
confidence: 99%
“…Revealing these mechanisms will help us understand how and where selection acts to shape diversity in immunological and life history investments (Zera and Harshman, 2001). Moreover, uncovering the mechanisms responsible for this diversity may help identify predictive biomarkers of host resistance (Poland et al, 2008;Vollmer-Conna et al, 2008), clarify the impact of different parasitic organisms on host defenses (Jackson et al, 2009), and provide important tools for forecasting and mitigating the spread of wildlife diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Mite-induced immuno-modulation of the host is a possibility (Jackson et al, 2009) and recent research suggests that D. gallinae both adapts its reproductive behaviour to the host (Harrington et al, 2010a) and modulates the host initial inflammatory responses (Harrington et al, 2010a,b). An understanding of the immunology of the D. gallinae-host relationship is important where vaccination is proposed as a control measure, yet despite the importance of D. gallinae in poultry production there is a lack of understanding of how the mite modulates and/or stimulates host immunity.…”
Section: Vaccinesmentioning
confidence: 99%